Cooling performance of two-phase closed thermosyphons installed at a highway embankment in permafrost regions. (5th April 2016) - Yu, Fan; Qi, Jilin; Zhang, Mingyi; Lai, Yuanming; Yao, Xiaoliang; Liu, Yongzhi; Wu, Guilong
Highlights: Long-term monitored data are presented for a road section of the Qinghai-Tibet Highway before and after installing the TPCTs. Cooling scope and period of the TPCTs are analyzed; cooling effects for the soil layers are examined. Cooling performance of the TPCTs is discussed from the perspectives of embankment deformation and crack formation. Some suggestions are proposed for a better design of the TPCTs in highway constructions in permafrost regions. Abstract: Two-phase closed thermosyphon (TPCT) is a popular way to prevent permafrost layers from degrading, and consequently ensure the stabilities of engineering constructions in permafrost regions. Although TPCTs have been numerically and experimentally investigated for many years, long-term field monitored data concerning the cooling performance of TPCTs are limited. This paper presents the ground temperatures, embankment deformations and some related meteorological factors for a road section of the Qinghai–Tibet Highway before and after installing the TPCTs in permafrost regions. Based on the monitored data, three main aspects are analyzed: 1) cooling scope and period of the TPCTs; 2) cooling effects for the soil layers, especially for the permafrost layers; and 3) remedying effects with respect to embankment deformation and crack formation. Some corresponding suggestions are proposed for a better design of TPCTs in the construction of roadways in permafrost regions.